Journal on Data Semantics XIV - Spaccapietra, Stefano; Delcambre, Lois.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
The LNCS Journal on Data Semantics is devoted to the presentation of notable work that, in one way or another, addresses research and development on issues related to data semantics. The scope of the journal ranges from theories supporting the formal definition of semantic content to innovative domain-specific applications of semantic knowledge. The journal addresses researchers and advanced practitioners working on the semantic web, interoperability, mobile information services, data warehousing, knowledge representation and reasoning, conceptual database modeling, ontologies, and artificial intelligence. Volume XIV results from a rigorous selection among 21 full papers received in response to a call for contributions issued in September 2008.
Defining the Semantics of Conceptual Modeling Concepts for 3D Complex Objects in Virtual Reality -- Towards a General Framework for Effective Solutions to the Data Mapping Problem -- Using Semantic Networks and Context in Search for Relevant Software Engineering Artifacts -- Applying Fuzzy DLs in the Extraction of Image Semantics -- MISM: A Platform for Model-Independent Solutions to Model Management Problems.
Keywords: Computer science; Computers; Database management; Data mining; Information storage and retrieval; Artificial intelligence; Computer Science; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Database Management; Information Systems Applications (incl. Internet).; Models and Principles; Electronic books